The Development of Indonesian Marriage Law in Contemporary Era - Nurul Miqat; Handar Subhandi Bakhtiar; Safrin Salam; Kunthi Tridewiyanti; Kayode Muhammed Ibrahim (De Jure: Jurnal Hukum dan Syari'ah, 2023)
Family law is part of the legal system that applies in Indonesia, which has developed along with social developments in society. This paper provides an overview of how the development of family law in Indonesia uses a normative approach and describes the development of family law in Indonesia these days. The development of family law in Indonesia is influenced by several factors, ranging from the historical aspect of law to today's social developments. The development of family law develops according to the community's needs for legal certainty and aspects related to family relations, starting from age limits for prospective husbands and prospective wives, child status, and marriage agreements to a marital status that is not administratively registered.